Multiple Pulp Stones in Primary and Developing Permanent Dentition: A Report of 4 Cases - Mohita Marwaha; Radhika Chopra; Payal Chaudhuri; Atul Gupta; Jayna Sachdev (Hindawi Limited, 2012)
Pulp stones are foci of calcification or discrete calcifications in the dental pulp. They are frequently found on bitewing and periapical radiographs, but their occurrence in entire dentition is unusual. We are reporting four cases in which the occurrence of pulp stones ranged from their presence in just primary teeth (Cases 1 and 2) to involvement of young permanent teeth also (Case 3) and even unerupted permanent teeth (Case 4). In all the cases, dental, medical, and family histories as well as the findings from the clinical examination of the patient were not contributory. Histopathological report revealed true denticle. Metabolic evaluation of patients through liver function test, kidney function test, and blood investigation did not show any metabolic disorders. Patients were also evaluated for any systemic, syndromic, or genetic involvement, but this was also noncontributing. Therefore, it is suggested that these unusual cases may be of idiopathic origin.